Phagocytosis and induction of nitric oxide synthase in murine macrophages. - Cunha, F Q (1993)
The murine macrophage cell line, J774, produced little or no detectable levels of nitric oxide (NO) when stimulated with interferon-gamma (IFN-gamma) alone in vitro. However, they expressed high levels of NO synthase and produced large amounts of NO when cultured with IFN-gamma in the presence of lipopolysaccharide (LPS). The synergistic action of LPS can be replaced by ingestion by the macrophages of zymosan, Staphylococcus aureus or Leishmania major in a dose-dependent manner. In contrast, the ingestion of particles such as latex beads or silica in the presence of IFN-gamma did not lead to the induction of NO synthase activity. Furthermore, ingestion of ink particles significantly reduced the ability of the macrophages to express NO synthase in response to the optimal stimulation of IFN-gamma and LPS. These results therefore demonstrate that phagocytosis per se is not sufficient to provide the additional signal for the induction of NO synthase activity in macrophages by IFN-gamma, and that the ingestion of certain particles can lead to the paralysis of the expression of this enzyme.